Analyzing the Impact of Financial Eporting on Investment Decisions: A Comparative Study of IFRS and GAAP in Vietnam - Khanh, Thai Hong Thuy; Rajagopal, Premkumar; Singh, Harwindar; Hoang, Trinh Xuan (Journal of Ecohumanism, 2024)
In the context of globalization and the rapid development of international capital markets, the quality of financial information has become extremely important. As Vietnam continues its international economic integration, the country faces both challenges and opportunities in adopting International Financial Reporting Standards (IFRS), which are currently mandatory in over 140 countries, including the European Union, Australia, and several countries in Asia (IFRS, 2024). Many nations have voluntarily adopted IFRS, recognizing its role in enhancing global competitiveness and strengthening investor confidence. The Ministry of Finance of Vietnam, through Decision 345/QĐ-BTC, has laid out a two-phase plan for IFRS adoption: voluntary until 2025 and mandatory from 2025 onwards. To meet these deadlines, companies must adjust not only their accounting systems but also their processes and human resources to be able to prepare IFRS-compliant financial statements by 2025. Globally, the standardization of financial reporting aims to improve the quality and comparability of financial data, thus supporting investment decision-making. This research explores the impact of IFRS and GAAP in Vietnam, a transitioning economy, examining how these standards affect transparency, reliability, and investor behavior. By highlighting the differences between IFRS and GAAP, as well as their effects on investment strategies, the research contributes to the development of better financial management policies, which is a critical factor in Vietnam's economic integration efforts.